LOVE IN A TIME OF SCARCITY - Chris Hermans (Acta Theologica)
Love as a theological virtue raises difficult questions. How can love be a gift from God, and yet at the same time human beings can be praised for the love of others? How can love be infused by God, and also be an act of free will? An event-hermeneutical approach can help us to find answers to these questions. This article presents an event-hermeneutical reading of the parable of the prodigal son, and the phenomenological analysis of love by Harry Frankfurt. The fact that a person comes to love the object of his love implies a deep transformation of the will. But love is a risk: it may happen, but it need not. The (im)possibility of transformation is deepened by looking at the phenomenon of scarcity. At the end of the article, the author summarises five elements of a theological theory on the virtue of love in a time of scarcity.